Whither Transcendence? Immanence and Critique in The Self-Emptying Subject. - Jarada, Mohamad (Sophia, 2024)
This paper engages Alex Dubilet's The Self-Emptying Subject: Kenosis and Immanence, Medieval to Modern and his account of immanence and kenosis as exhibited in his reading of Hegel's concept of Entäußerung [externalization]. Specifically, I focus on the "problematic of desubjectivation" that centers Dubilet's critique of transcendence and its relationship to subjection and subjectivity. I reconsider the relationship made between this problematic, the ethics of kenosis, and the concept of immanence so as to demonstrate the ways in which Dubilet attempts to depart from transcendence, subjectivity, and their concomitant ethics. In particular, I consider his reading of Hegel's concept of Entäußerung and its similarities to the Young Hegelians' understanding of this concept. My reading of Dubilet suggests that while he seeks to depart from transcendence, he reintroduces transcendence through the "problematic of desubjectivation" and its relationship to kenosis. In conclusion, I question the philosophical import of immanence in contemporary critical inquiry and why its conceptualization is often positioned in opposition to transcendence.